2011
DOI: 10.1627/jpi.54.380
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oxidative Esterification of Propionaldehyde to Methyl Propionate Using Heavy-metal-free Palladium Catalysts under Pressurized Oxygen

Abstract: The use of pressurized oxygen greatly enhanced catalytic activity for oxidative esterification of propionaldehyde to methyl propionate with methanol using heavy-metal-free Pd/C and Pd/Al2O3. For example, the conversion of propionaldehyde, the selectivity to methyl propionate, and the yield of the propionate using 5 % Pd/Al2O3 were 99.9, 62.7, and 62.6 %, respectively, at 1.5 MPa of oxygen gas and 333 K. This result demonstrated that Pb doping of Pd catalysts was not needed to achieve comparable activity, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Symbols: ○, the conversion of PA; □, the selectivity to MP; △ , the yield of MP; and closed bar, the MP As shown in Figure 2, the conversion of PA increased with the reaction time while the selectivity to MP was essentially constant regardless of the reaction time, which resulted in an increase in the yield of MP. During the conversion of PA, the selectivity to MP, and the yield of MP after 6 h were 99.9, 61.9 and 61.8%, respectively, which was essentially identical to the activity reported under the same conditions (99.9, 62.7 and 62.6%, respectively) in our previous paper (Sugiyama et al, 2011). This data was evidently lower than that (93.2, 76.8 and 71.6%, respectively) reported by Diao et al (2009) at 0.3 MPa of O 2 and 353 K after 2 h, although the reaction temperature in the present reaction was 20 K lower than that reported by Diao et al (2009), and the weight of the catalyst (1.0 g) was four-fold greater than that reported by Diao et al (2009).…”
Section: Figsupporting
confidence: 89%
See 4 more Smart Citations
“…Symbols: ○, the conversion of PA; □, the selectivity to MP; △ , the yield of MP; and closed bar, the MP As shown in Figure 2, the conversion of PA increased with the reaction time while the selectivity to MP was essentially constant regardless of the reaction time, which resulted in an increase in the yield of MP. During the conversion of PA, the selectivity to MP, and the yield of MP after 6 h were 99.9, 61.9 and 61.8%, respectively, which was essentially identical to the activity reported under the same conditions (99.9, 62.7 and 62.6%, respectively) in our previous paper (Sugiyama et al, 2011). This data was evidently lower than that (93.2, 76.8 and 71.6%, respectively) reported by Diao et al (2009) at 0.3 MPa of O 2 and 353 K after 2 h, although the reaction temperature in the present reaction was 20 K lower than that reported by Diao et al (2009), and the weight of the catalyst (1.0 g) was four-fold greater than that reported by Diao et al (2009).…”
Section: Figsupporting
confidence: 89%
“…As pointed out in Section 2.1., the surface area and dispersion of the Pd metal contributed to the catalytic activity. However, as shown in our previous paper (Sugiyama et al, 2011), the activity of Pd/C, with a greater surface area (946 m 2 /g) and a greater dispersion of Pd (13.9%), was evidently lower than that using Pd/Al 2 O 3 . This indicated that the nature of the influence of Pd over the supports, C and Al 2 O 3 , might have differed.…”
Section: Xafs Analysis Of the Pd Species On Pd/c And Pd/al 2 Osupporting
confidence: 60%
See 3 more Smart Citations